"I feel I'm leading the charge." Experiences of a virtual physiotherapist-guided knee health program for persons at-risk of osteoarthritis after a sport-related knee injury. Issue 1 (March 2023) - Truong, Linda K.; Mosewich, Amber D.; Miciak, Maxi; Pajkic, Andrea; Silvester-Lee, Trish; Li, Linda C.; Whittaker, Jackie L.
Abstract: Objective: Describe participants' perspectives about the feasibility of a virtual, physiotherapist-guided knee health program for people at risk of post-traumatic osteoarthritis after a sport-related knee injury. Design: Qualitative description study nested within a quasi-experimental study evaluating the feasibility of the Stop OsteoARthritis (SOAR) with persons with sport-related knee injuries. SOAR includes: 1) one-time Knee Camp (group education, 1:1 exercise/activity goal-setting); 2) weekly home-based exercise/activity program with tracking, and; 3) weekly 1:1 physiotherapy-guided action-planning. Upon program completion, semi-structured 1:1 interviews were conducted with participants identified by convenience and maximum variation sampling (age, gender, program satisfaction). Open-ended questions elicited participants' experiences with the program. Content analysis was conducted. Results: 12 women and 4 men [median (min-max) age; 30 (19–46) years] were interviewed. Four categories depicted participants' experiences: 1) ' SOAR satisfies an unmet need' portrayed the perceived relevance and need for a program that promotes knowledge about knee health and self-efficacy for independent exercise behaviour, 2) ' Regaining control of knee health' described how SOAR empowered participants and fostered a sense of 'leading the charge' to their own knee health, 3) 'Social support encourages exercise participation' highlighted that weekly physiotherapy interactions provided accountability for achieving exercise goals, and that relating to other participants was inspirational, 4) 'Program refinements and barriers' suggested enhancements to meet the needs of future participants. Conclusions: Participants report the SOAR program to be acceptable, relevant, and empowering. Improved knowledge about one's knee health, self-efficacy, autonomy, and social support may encourage exercise adherence and self-management of future knee OA risk.